An Examination of Income Inequality Trends and Patterns Across Different Socioeconomic Groups - Aamer Nabi Ganaie; Irshad Ahmad Reshi (RADJA PUBLIKA, 2023)
Understanding the complex nature of income disparity requires looking at its patterns and trends across demographics, and this essay does just that. The unequal distribution of income between people and households has serious economic and social consequences. This research tries to illuminate these inequalities by examining them from an economic perspective. Measures of income inequality such as the Gini coefficient and the Palma ratio are among those examined in this article. The socioeconomic gradient, a method of classifying people according to their income, education, and occupation, is also studied. Trends and patterns in economic disparity through time are shown by examining historical data, with contributors like education, globalisation, and access to basic amenities being singled out. Implications for policymaking are examined, with an emphasis on the need for solutions that get at the heart of the problems that have led to widespread income disparity. Societies can move towards a more just and equitable future through promoting economic equity and boosting social mobility.